(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article examines the problems of the functioning of economic diplomacy in Ukraine and its effectiveness in the conditions of war. Theoretical approaches to the definition of "economic diplomacy" in foreign and national scientific sources were characterized. The components of economic diplomacy, promulgated by the Law of Ukraine "On the Principles of Internal and Foreign Policy" and the Law of Ukraine "On National Security" and their actualization in the conditions of modern global challenges, the biggest of which are the problems in Ukraine, were determined. Examples of Ukraine’s economic diplomacy during the war were given, namely: increased pressure on international partners to impose sanctions on the aggressor country, which will limit Russia’s access to financial markets, high technologies, and energy resources, which directly affects the aggressor’s economy; establishment of the "grain corridor", which began its work in July 2022 with the mediation of the Turkey and UN, and is still working today, despite Russia’s withdrawal from the "grain agreement"; negotiations with international partners regarding investments in the reconstruction of infrastructure and the economy after the war; cooperation with international partners regarding the development of alternative logistics routes through land borders with the European Union, in particular through Poland, Romania, and other countries; diplomatic efforts to obtain humanitarian and material aid from the international community for the affected population as a result of the war, etc. It was emphasized that at the current stage, the economic diplomacy of Ukraine is a key tool for overcoming both internal and external challenges caused by the military aggression of the RF. It was concluded that global changes, the strengthening of economic sanctions, the need to restore the national infrastructure, and integration into world markets require Ukraine to have an effective foreign economic policy. Implementing such a policy is possible only with the support of active economic diplomacy.